An In Vitro Comparison of the Shear Bond Strengths of Two Different Gingiva‐Colored Materials Bonded to Commercially Pure Titanium and Acrylic Artificial Teeth. Issue 4 (12th February 2014) - Elzarug, Yahya A.M.; Galburt, Roger B.; Ali, Ala; Finkelman, Matthew; Dam, Hamasat Gheddaf
Abstract Purpose The purpose of this study was to compare shear bond strengths between two different gingiva‐colored materials bonded to titanium alloy discs and acrylic resin artificial teeth. Materials and Methods For the first part of this study, 30 titanium alloy disc specimens were embedded in autopolymerizing resin. These discs were then divided randomly into two groups: Heat Cure (HT1) and Pink Composite (CT1). The discs were sandblasted with 100 μm aluminum oxide particles. For the HT1 group using silicone molds, a wax‐up was performed. After the wax removal step, heat‐cured acrylic resin was applied and processed according to the manufacturer's recommendations. For the CT1 group using silicone molds, metal primer II and gum opaque were applied and light cured; pink composite was then applied and light cured. For the second part of the study, 30 artificial resin first molar teeth were completely embedded in autopolymerizing resin. Teeth were then divided randomly into two groups: Heat Cure (HT2) and Pink Composite (CT2). For the HT2 group using silicone molds, wax‐up was performed. Specimens were then transferred to be processed in the heat‐cured acrylic resin according to the manufacturer's recommendations. For the CT2 group using silicone molds, composite primer followed by pink composite were applied and light cured. Shear bond tests were performed using an Instron 3345 universal testing machine. The shear load at the point of failure was recorded in Newtons. The force was calculated in MPa by calculating the failure load divided by the surface area. Two independent‐samples t‐tests were performed. A significance level of p < 0.05 was used for comparison. Results This study revealed that the difference in the shear bond strengths of two different gingiva‐colored materials bonded to titanium discs was statistically significant (p = 0.012). The difference in the shear bond strengths of two different gingival‐colored materials bonded to acrylic teeth was statistically significant (p < 0.001). Conclusion In this in vitro study, heat‐cured acrylic resins exhibited higher bonding strengths when bonded to titanium discs or acrylic artificial teeth in comparison to pink composite resins.